Leveraging Online Learning to Promote Systems Thinking for Sustainable Food Systems Training in Dietetics Education - Spiker, Marie; Hege, Amanda; Giddens, Janice; Cummings, Joanna; Steinmetz, Jasia; Tagtow, Angie; Bergquist, Erin; Burns, Lauren; Campbell, Christina; Stadler, Diane; Combs, Elizabeth; Prange, Nancy; et al. (Frontiers in Nutrition, 2021)
Educating and training a multisectoral food systems workforce is a critical part of developing sustainable, resilient, and healthy food and water systems. This paper shares perspectives from a working group of educators, learners, and food systems subject matter experts that collaborated over the course of a year to develop, pilot test, and evaluate two interactive webinar series with a multi-site cohort of dietetics interns and graduate students. The three-part webinar series format included a training webinar, a practice activity, and a synthesis webinar. In reflecting on the effectiveness of this format, we provide direct assessments of student learning from subject matter experts alongside indirect assessments from pre- and post-surveys fielded with learners. Learners who participated in an interactive webinar series demonstrated skills in several dimensions of systems thinking and gained confidence in food systems learning outcomes. Learners also shared valuable feedback on the opportunities and challenges of using online platforms for this experience. As online learning opportunities become more common, it will become increasingly important for educators to prioritize strategies that effectively equip students with the higher-order thinking skills, such as systems thinking, needed to address the complexities of sustainable food systems. The interactive webinar series format described here provides an opportunity to leverage didactic webinars in combination with interactive experiences that enable learners to deepen their knowledge through practice with peers and subject matter experts. Though this format was piloted within dietetics education programs, many of the lessons learned are transferable to other food systems educational contexts.